2016
DOI: 10.5194/acp-16-4987-2016
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical properties in the southeastern United States in summer – Part 1: Hygroscopic growth

Abstract: Abstract. Aircraft observations of meteorological, trace gas, and aerosol properties were made during MaySeptember 2013 in the southeastern United States (US) under fair-weather, afternoon conditions with well-defined planetary boundary layer structure. Optical extinction at 532 nm was directly measured at relative humidities (RHs) of ∼ 15, ∼ 70, and ∼ 90 % and compared with extinction calculated from measurements of aerosol composition and size distribution using the κ-Köhler approximation for hygroscopic gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 100 publications
(137 reference statements)
5
98
0
Order By: Relevance
“…In this study, we estimated γ values with observed f (RH) curves and to our knowledge, we are the first ones to further examine the relationship between γ and κ f (RH) . Recently, a new physically based single-parameter representation was proposed by Brock et al (2016) to describe f (RH). Their results demonstrated that this proposed parameterization scheme can better describe f (RH) than the widely used gamma power-law approximation (Brock et al, 2016).…”
Section: Parameterization Schemes For F (Rh)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we estimated γ values with observed f (RH) curves and to our knowledge, we are the first ones to further examine the relationship between γ and κ f (RH) . Recently, a new physically based single-parameter representation was proposed by Brock et al (2016) to describe f (RH). Their results demonstrated that this proposed parameterization scheme can better describe f (RH) than the widely used gamma power-law approximation (Brock et al, 2016).…”
Section: Parameterization Schemes For F (Rh)mentioning
confidence: 99%
“…Recently, a new physically based single-parameter representation was proposed by Brock et al (2016) to describe f (RH). Their results demonstrated that this proposed parameterization scheme can better describe f (RH) than the widely used gamma power-law approximation (Brock et al, 2016). The formula of this new scheme is written as…”
Section: Parameterization Schemes For F (Rh)mentioning
confidence: 99%
See 1 more Smart Citation
“…The UHSAS uses a high-intensity infrared laser (semiconductor-diode-pumped solid-state neodymiumdoped yttrium lithium fluoride, Nd 3+ :Y LiF 4 , operating at 1054 nm with intra-cavity circulating power of ∼ 1 kW cm −2 ), an inlet jet assembly, and two detection systems: a highly sensitive avalanche photodiode (APD) to detect and size the smallest particles, and a less sensitive secondary PIN photodiode to size larger particles (Fig. 1) (Brock et al, 2016). This geometry contrasts with that reported by Cai et al (2008), who used scattering angles from 22 to 158 • to simulate UHSAS response.…”
Section: Operating Principlesmentioning
confidence: 99%
“…These sample treatments are not possible with the compact, wing-mounted instrument. The ground-type UH-SAS has been deployed in various airborne-based campaigns (Brock et al, 2011(Brock et al, , 2016Kassianov et al, 2015;Yokelson et al, 2011). However, as reported by Brock et al (2011), modifications to the flow system are required to make them suitable for airborne sampling.…”
mentioning
confidence: 99%